Simultaneous removal of a tumour of the right atrium and inferior vena cava and coronary bypass-grafting in a patient with recurrent clear renal cell carcinoma - Pietrzyk, Edward; Głuszek, Stanisław; Michta, Kamil; Gorczyca-Michta, Iwona; Kot, Marta; Wożakowska-Kapłon, Beata (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Metastatic cardiac tumours are the most common malignant cardiac tumours. In the early stages they are usually asymptomatic, but their consequences can be very serious, and the prognosis is poor. We present a patient with recurrent renal cell carcinoma as a tumour of the right atrium and the vena cava inferior in whom cancerous masses were removed with simultaneously coronary artery bypass-grafting.